Mathematical Modeling to Estimate Non-Tax State Revenues - Rahadatul Aisyi; Friska Anzalni; Yusuf Fajar; Didi Suhaedi; Erwin Harahap (International Journal of Quantitative Research and Modeling, 2022)
Mathematics is the basic foundation for other sciences. Equation is a mathematical model that can describe real-life problems, one of which is estimating non-tax state revenues in the coming year. Non-State Revenue (penerimaan negara bukan pajak, PNBP) is the scope of state finances which is equipped with the State Assets and Auction Service Office (kantor pelayanan keuangan negara dan lelang, KPKNL) which must be reported on the realization of PNBP that will be deposited into the state treasury. Such situation happens because expenditures in each government agency will be available and increase every year by the government. Therefore, direktorat jenderal keuangan negara (DJKN) have to be more optimal in the management of the PNBP. This study aims to determine the results of the best estimates and exponential models in estimating non-tax state income at the KPKNL Bandung, Indonesia, in year of 2017 and 2018. This research includes descriptive research using a qualitative approach. The results show that the calculation using the exponential 4th model is the best model for estimating PNBP such that the estimated PNBP results in 2017 is Rp. 574,775,677 and in 2018 is Rp. 798,022,691.